Professional and Pedagogic Competence of Lecturers of the Faculty of Engineering Universitas Negeri Manado - Telly Tangkere (JR Education, 2022)
The four teacher competencies are very important and cannot be separated from one another. Professional competence, pedagogic competence, social competence and personality competence. One competency complements other competencies, so there is no more major competency. Assessing overall competence has often been done, especially with regard to professional competence. The author is interested in discussing specifically about pedagogic competence, with the assumption that professional competence will be meaningless if a teacher cannot carry out the learning process using methodical didactics. In other words, professional competence will not have any effect without understanding pedagogic competence. Pedagogic competence actually when applied correctly contains elements of other competencies, both professional, social and personality. Teacher competence, does not necessarily happen without a certain ability to be taught, then teaching competence must be followed by a strong basis as a form of social and personality abilities. The competence of lecturers, of course, has always focused on professional abilities in accordance with their fields of expertise, even as if ignoring other competencies. These conditions will be a problem when applying and the condition of students who are not ready. A good teaching ability must of course be supported by an expertise, which makes him a teacher. If as an instructor, this is not a problem, but when knowledge and skills must be shared with students, the problem arises how to do it, especially for students with vocational characteristics. Optimal learning quality produces good achievement for students. Many factors are the cause so that students are not satisfied in learning in class/school and of course become an obstacle to student achievement. In addition to psychological factors and internal factors, there are also other external factors. Therefore, researchers are interested in studying specifically pedagogic competence, so that the problem in this study is the Professional and Pedagogic Competence of Faculty of Technology Unima Lecturers. How is the level of professional and pedagogic competence of Faculty of Technology Unima Lecturers?. Are there differences in the competence of female and male lecturers?